2015
DOI: 10.1186/s12885-015-1287-9
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of non-medical determinants of adherence to R-CHOP therapy for diffuse large B-cell lymphoma: implication for survival

Abstract: BackgroundAdherence to therapy has been established for years as a critical parameter for clinical benefit in medical oncology. This study aimed to assess, in the current practice, the influence of the socio-demographical characteristics and the place of treatment on treatment adherence and overall survival among diffuse large B-cell lymphoma patients.MethodsWe analysed data from 380 patients enrolled in a French multi-centre regional cohort, with diffuse large B-cell lymphoma receiving first-line treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…36,37 Only one study published in 2014 evaluated the role of SES in specific DLBCL survival. 23 In contrast to our results, the authors reported lower DLBCL survival in patients with a lower SES, with the association being more pronounced in the modern treatment era after the introduction of rituximab and in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Only one study published in 2014 evaluated the role of SES in specific DLBCL survival. 23 In contrast to our results, the authors reported lower DLBCL survival in patients with a lower SES, with the association being more pronounced in the modern treatment era after the introduction of rituximab and in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Depending on local practice guidelines, R-CHOP is typically administered for six or eight cycles 5,6 ; treatment adherence is important for optimal outcomes. 7 Although R-CHOP cures approximately 60% of patients, 8 outcomes remain poor for those who do not achieve complete remission or develop disease relapse, 8 with a median overall survival (OS) of less than 1 year after progression during first-line treatment. 9 Despite the development and testing of innovative therapies, none has outperformed R-CHOP in almost two decades.…”
Section: Introductionmentioning
confidence: 99%
“…However, the indices were more efficient at measuring individual income than education or occupational category and are suitable for measuring deprivation but not affluence [17]. Despite these limitations, EDI was used in previous paper to study social inequalities in cancer risk [20], incidence [21], treatment [22, 23], characteristics [24] or outcome [25] confirming the relevance of such index. Since its development in 2012, almost forty papers using the European Deprivation Index (EDI) was published up to the first quarter of 2019.…”
Section: Discussionmentioning
confidence: 99%